(untitled) (Revista científica Olimpia, 2026)
This research examines the legal effects of sports naturalization in Ecuador, analyzing how the absence of a comprehensive legal framework impacts the development of local talent. The study aimed to evaluate the regulatory gap and its consequences on the fairness of competitions and the opportunities available to native athletes. A qualitative approach was applied with a dogmatic-legal and documentary design, analyzing the Constitution of the Republic of Ecuador, the Sports Law, and federation regulations, complemented by the analysis of specialized doctrine. The main findings demonstrate that deregulation has created high discretion, which correlates with a decrease in playing time for Ecuadorian athletes and the prevalence of economic interests over sporting ones. It is concluded that the State must implement specific and transparent regulations that harmonize the pursuit of competitiveness with the promotion of local talent, ensuring a balance that the current system does not offer. The research contributes to the formulation of fairer and more efficient sports policies.